Strategi Guru dalam Mengingkatkan Minat Belajar Siswa di Era Society 5.0 - Anggraini, Nunuk; Putra, Muhammad Alamsyah; Badriyah, Laila (CV Era Digital Nusantara, 2024)
Information and communication technology is developing rapidly and has the potential to change civilization. Society 5.0 has been revived by the Indonesian government as part of efforts for equality during the current industrial revolution. The Japanese government defines an era known as “Society 5.0”, which is based on ideas that advance society technologically and are human-centered. Modern society presents challenges as well as opportunities for people, especially students, to develop their soft skills in order to increase their learning capacity and interest in learning, so that they can become assets for the future. Apart from that, as we all know, the focus of education is currently balanced, with the internet functioning as a source of information and guidance in everyday life. The author uses qualitative research with a library study method. The purpose of writing this article is to find out what teachers' strategies in the Era of Society 5.0 are to increase students' interest in learning. Easy and fun learning can increase students' interest in learning during the learning process. The increase in students' interest in learning can be proven by the students' active response when the teacher is explaining the lesson.